Lichtenstein Versus Desarda’s Technique of Hernia Repair - Md Fardhus, -; Sharfuzzaman, AMSM; Dewan, Md Nayeem; Hossain, Md Abul; Hasan, Ahmed Sami Al; Rab, Joy Zauharia (Journal of Surgical Sciences, 2020)
Aim: To compare Desarda’s versus Lichtenstein’s mesh repair in patients with unilateral, primary, reducible inguinal hernia in terms of mean operative time and seroma formation Methods: This randomized control trial conducted at Department of Surgery, Patuakhali Medical College & Hospital, Patuakhali. Eighty patients with unilateral, primary, reducible inguinal hernia were randomly distributed into two groups to undergo hernia repair i.e. Lichtenstein (L) and Desarda’s (D). Outcome was measured in terms of mean operative time and seroma formation. Seroma formation was defined as presence of enclosed cavity containing serous fluid determined by ultrasonography at 30th post-operative day. Results: Thirty three patients (41.25%) were above 50 years of age, whereas remaining 47 patients (58.75%) were below 50 years of age. Five patients (6.25%) were female and 75 patients(93.75%) were male. Seroma formation was 5% in Desarda’s group while 7.5% in Lichtenstein group (P> 0.05). Similarly difference in mean operative time was statistically non-significant. Seroma formation was common in older age group. There was no effect of smoking, obesity, operative time and gender on seroma formation. Conclusion: It is concluded that there is no difference in frequency of seroma formation and mean operative time in Desarda’s or Lichtenstein’s technique of hernia repair. Journal of Surgical Sciences (2018) Vol. 22 (2) : 99-103